Anisotropy characteristics of element composition in Upper Triassic "Chang 8" shale in Jiyuan district of Ordos Basin, China: Microscopic evidence for the existence of predominant fracture zone. (1st October 2019) - Du, Shuheng; Xu, Feng; Taskyn, Abitkazy; Zhou, Bo; Kou, Gen; Shi, Yongmin
Abstract: This study quantified the anisotropy of element composition in Upper Triassic "Chang 8" shale in Jiyuan district of Ordos Basin, China and provided the microscopic evidence for the existence of dominant fracture zone. Element quantification was carried out ensuring both observational resolution and sample representativeness. Results show that for shale slices in two directions which are 45° (225°) and 0° (180°/360°), the distribution of elements is significantly different from that in other directions. The minimum of element contents often occurs in 45° (225°) and the maximum of element contents often occurs in 0° (180°/360°). The brittleness parameter value stays at a high level from 0° (180°/360°) to 22.5° (202.5°). The maximum value occurs in 0° (180°/360°), and the minimum value occurs in 45° (225°) which has obvious significance in shale stimulation. The conclusion proved that the existence of predominant fracture zone in shale has the microscopic evidence in micro-scale brittle minerals.